2021
DOI: 10.3847/1538-4357/ac05c2
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison between Nuclear Ring Star Formation in LIRGs and in Normal Galaxies with the Very Large Array

Abstract: Nuclear rings are excellent laboratories for studying intense star formation. We present results from a study of nuclear star-forming rings in five nearby normal galaxies from the Star Formation in Radio Survey (SFRS) and four local LIRGs from the Great Observatories All-sky LIRG Survey at sub-kiloparsec resolutions using Very Large Array high-frequency radio continuum observations. We find that nuclear ring star formation (NRSF) contributes 49%-60% of the total star formation of the LIRGs, compared to 7%-40% … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 117 publications
5
22
0
Order By: Relevance
“…Other studies directly suggest that one cannot use rest-optical lines to estimate physical properties of entire starburst systems, and one should instead aim to obtain rest-frame near-IR observations (Puglisi et al 2017;Calabrò et al 2018). Other recent works have used radio emission (specifically free-free emission) to measure star formation, in addition to IR and recombination lines (e.g., Murphy et al 2018;Linden et al 2019Linden et al , 2021Song et al 2021). Freefree emission does not have the caveat of being affected by extinction as is the case for recombination lines.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies directly suggest that one cannot use rest-optical lines to estimate physical properties of entire starburst systems, and one should instead aim to obtain rest-frame near-IR observations (Puglisi et al 2017;Calabrò et al 2018). Other recent works have used radio emission (specifically free-free emission) to measure star formation, in addition to IR and recombination lines (e.g., Murphy et al 2018;Linden et al 2019Linden et al , 2021Song et al 2021). Freefree emission does not have the caveat of being affected by extinction as is the case for recombination lines.…”
Section: Introductionmentioning
confidence: 99%
“…To ensure that we only identify physically meaningful structures, we ran Astrodendro on both the 15 and 33 GHz images of each system with min_value = 5σ rms and min_delta = 1σ rms where σ rms is the rms noise measured in an emission-free region of the image before primary-beam correction. We follow Song et al (2021) and set min_npix to be a quarter of the area of the synthesized beam, to avoid identifying noise spikes yet allowing detection of small unresolved regions. Despite that extended diffuse emission is largely filtered out in these observations, complex structures encompassing trunk, branch, and leaf are identified in several systems.…”
Section: Regions Identification and Measurementsmentioning
confidence: 99%
“…of heavily obscured luminous AGNs in local U/LIRGs (Iwasawa et al 2011;Treister et al 2012;Ricci et al 2017Ricci et al , 2021Koss et al 2018;Torres-Albà et al 2018) has provided strong supporting evidence for this evolutionary scenario (see also review by U 2022), details regarding the interplay between star formation and AGN activity, as well as how they together (or separately) act upon the transformation of these extreme systems, still remain ambiguous. However, the extraordinary star-forming properties of local U/LIRGs relative to nearby normal galaxies (i.e., galaxies with L IR < 10 11 L e ; e.g., Lonsdale et al 1984;Howell et al 2010;Stierwalt et al 2014;Piqueras López et al 2016;Díaz-Santos et al 2017;Linden et al 2019Linden et al , 2021Larson et al 2020;Song et al 2021), and the prevalence of outflows observed in starburst-dominated local U/LIRGs (e.g., Rupke et al 2005;Cazzoli et al 2016;Barcos-Muñoz et al 2018;Fluetsch et al 2019Fluetsch et al , 2020Vivian et al 2019) highlight the pivotal role of star-formation-driven feedback in regulating their evolution. To better quantify the physical processes governing the evolution of local U/LIRGs, a robust characterization of the most energetic regions in these systems is necessary.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations